Pattern of and clinicopathologic risk factors for lateral lymph node metastases in papillary thyroid carcinoma patients with lateral cervical lymphadenopathy. Issue 36 (September 2018) - Gong, Yanping; Yang, Jing; Yan, Shuping; Su, Anping; liu, Feng; Gong, Rixiang; Zhu, Jingqiang; Li, Zhihui
Abstract : Abstract: The surgical extension of lateral neck dissection (LND) in papillary thyroid carcinoma (PTC) with clinical lateral lymph node metastases (LLNM) remains controversial. The aim of this study was to explore the pattern of and clinicopathologic risk factors for LLNM in PTC with clinical unilateral LND to determine the rational extent of therapeutic LND. This retrospective study reviewed the records of 246 consecutive patients with PTC who simultaneously underwent total thyroidectomy, bilateral central lymph node dissection, and unilateral therapeutic LND. The frequency and pattern of LLNM were analyzed. Grossly, LLNM were present in 80.9% of patients, and level II to V lymph node metastases (LNM) were present in 45.9%, 62.6%, 56.1%, and 11.8% patients, respectively. Superior tumor location, extrathyroidal extension, and ipsilateral, contralateral, and bilateral central LNM (CLNM) were independent risk factors for gross LLNM. Age ≥45 years, superior lobe tumors, extrathyroidal extension, and ipsilateral and contralateral CLNM were independent risk factors for level II LNM. Age ≥45 years, superior and middle lobe tumors, extrathyroidal extension, and ipsilateral CLNM were independent risk factors for level III LNM. Superior lobe tumors and ipsilateral, contralateral, and bilateral CLNM were independent risk factors for level IV LNM. Only contralateral CLNM was an independent risk factor for level V LNM. In PTC patients with clinical LLNM, the predominant sites of LLNM were levels II to IV and not level V. Therapeutic elective LND should include the lateral nodal levels associated with independent risk factors, especially superior tumors location and CLNM.